2D Colloidal Atomic-Thick Metal Chalcogenides: Synthesis, Growth Mechanisms and Applications - Pang, Yingping (Curtin University, 2019)
In this thesis, we investigated a wide scope of atomically thin two-dimensional (2D) metal chalcogenide nanoparticles in terms of their synthetic methods, optical properties, and applications. A series of 2D metal chalcogenides, including ZnS, ZnSe, MoS2, WS2, and ReS2, were synthesized and their growth mechanisms (ZnS, ZnSe and MoS2) were elucidated underpinned by the theoretical simulations. The potential applications of such 2D nanoparticles in photodetection (ZnSe) and hydrogen evolution reaction (MoS2) were also systematically investigated, demonstrating their great potential in optoelectronic devices and solar-driven clean fuel production.